Rowing velocity prediction program with estimating hydrodynamic load acting on an oar blade - Kinoshita, T.; Miyashita, M.; Kobayashi, H.; Hino, T. (Bio-mechanisms of swimming and flying. Fluid dynamics, biomimetic robots, and sports science, 2008)
An oar blade behaves as unsteady hydrofoil and its load strongly depends on a reduced frequency of the rowing motion. The tank lest is carried out using a circulating water channel to estimate the load.